Recent advances in the combination of cellular therapy with stem cells and nanoparticles after a spinal cord injury - García, Elisa; Sánchez-Noriega, Samantha; González-Pacheco, Guadalupe; González-Vázquez, Alejandro Naat; Ibarra, Antonio; Rodríguez-Barrera, Roxana (Frontiers in Neurology, 2023)
Background Currently, combined therapies could help to reduce long-term sequelae of spinal cord injury (SCI); stem cell therapy at the site of injury in combination with other therapies has shown very promising results that can be transferred to the clinical field. Nanoparticles (NPs) are versatile technologies with applications to medical research for treatments of SCI since they could deliver therapeutic molecules to the target tissue and may help to reduce the side effects of non-targeted therapies. This article's purpose is to analyze and concisely describe the diverse cellular therapies in combination with NPs and their regenerative effect after SCI. Methods We reviewed the literature related to combinatory therapy for motor impairment following SCI that has been published by Web of Science, Scopus, EBSCO host, and PubMed databases. The research covers the databases from 2001 to December 2022. Result Animal models of SCI have shown that the combination of NPs plus stem cells has a positive impact on neuroprotection and neuroregeneration. Further research is required to better understand the effects and benefits of SCI on a clinical level; therefore, it is necessary to find and select the most effective molecules that are capable of exacerbating the neurorestorative effects of the different stem cells and then try them out on patients after SCI. On the other hand, we consider that synthetic polymers such as poly [lactic-co-glycolic acid] (PLGA) could be a candidate for the design of the first therapeutic strategy that combines NPs with stem cells in patients with SCI. The reasons for the selection are that PLGA has shown important advantages over other NPs, such as being biodegradable, having low toxicity levels, and high biocompatibility; In addition, researchers could control the release time and the biodegradation kinetics, and most importantly, it could be used as NMs on other clinical pathologies (12 studies on www.clinicaltrials.gov) and has been approved by the Federal Food, Drug, and Cosmetic Act (FDA). Conclusion The use of cellular therapy and NPs may be a worthwhile alternative for SCI therapy; however, it is expected that the data obtained from interventions after SCI reflect an important variability of molecules combined with NPs. Therefore, it is necessary to properly define the limits of this research to be able to continue to work on the same line. Consequently, the selection of a specific therapeutic molecule and type of NPs plus stem cells are crucial to evaluate its application in clinical trials.